A metabolic labeling way to in situ fabricate bacterial FRET platform for innate immune defence molecule - Zhang, Zhijun (2022)
A simple and unique bacterial fluorescence resonance energy transfer (FRET) platform is developed through metabolic biosynthetic pathways for the sensitive and ratiometric detection of innate immune defence molecule. Using this bacterial FRET platform, immune molecule lysozyme could be sensitively monitored in buffer, in serum, and even in the secretion of infected immune cells. As an important defensive molecule of the innate immune system, lysozyme not only plays a significant role in mediating protection against microbial invasion, but also acts as a significant biomarker of leukemia, tuberculosis, meningitis and renal diseases. Considering the importance of perceiving lysozyme activity, this work sheds a light on the access of host's immune response of bacterial infection, as well as provides valuable guidance for the treatment of bacterial infection related diseases.